2010
DOI: 10.1158/0008-5472.can-10-0258
|View full text |Cite
|
Sign up to set email alerts
|

Protein Tyrosine Phosphatase Receptor Type γ Is a Functional Tumor Suppressor Gene Specifically Downregulated in Chronic Myeloid Leukemia

Abstract: Chronic myelogenous leukemia (CML) is the most common myeloproliferative disease. Protein tyrosine phosphatase receptor type γ (PTPRG) is a tumor suppressor gene and a myeloid cell marker expressed by CD34 + cells. Downregulation of PTPRG increases colony formation in the PTPRG-positive megakaryocytic cell lines MEG-01 and LAMA-84 but has no effect in the PTPRG-negative cell lines K562 and KYO-1. Its overexpression has an oncosuppressive effect in all these cell lines and is associated with myeloid differentia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 39 publications
4
57
0
1
Order By: Relevance
“…The antigen is a glycoprotein, the epitopes of which can greatly influence the capability of the resulting antibodies to recognize the native antigen. We previously evaluated the capability of affinity-purified TPγ B9-2 to recognize the full-length protein by immunoprecipitation in the K562 cell line transfected with PTPRG cDNA [8]. Glioblastoma expresses one of the highest levels of PTPRG [19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antigen is a glycoprotein, the epitopes of which can greatly influence the capability of the resulting antibodies to recognize the native antigen. We previously evaluated the capability of affinity-purified TPγ B9-2 to recognize the full-length protein by immunoprecipitation in the K562 cell line transfected with PTPRG cDNA [8]. Glioblastoma expresses one of the highest levels of PTPRG [19].…”
Section: Resultsmentioning
confidence: 99%
“…Forced overexpression of PTPRG led to reduced tyrosine phosphorylation, decreased clonogenic capability, and induction of apoptosis in CML cells. In the same study, we have shown that BCR-ABL1, the key deregulated kinase in CML, is a biochemical substrate for PTPRG [8]. Two epitope-specific antisera against the extracellular domain (ECD) of PTPRG have previously been developed from rabbit [9] and chicken [10].…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, these observations suggest that KIT, ABL1, and BTK may be involved in LFA-1 affinity modulation by chemoattractants, perhaps concurrently cooperating with JAKs. Interestingly, ABL1 was already shown to be a direct PTPRG target (45). A role for these kinases in LFA-1 affinity modulation is unknown, and it will be of interest to investigate their involvement in leukocyte trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, many neoplastic cells modulate the expression of PTPRG (19). In this context, PTPRG has been recently proposed as a tumor suppressor gene involved in the pathogenesis of CML (45). Furthermore, KIT and ABL1, PTPRG targets, are oncogenes.…”
Section: Discussionmentioning
confidence: 99%
“…만성 골수성 백혈병은 모든 백혈 병의 약 15∼20%를 차지하고 100,000명에 1∼1.5명의 빈도로 발생한다고 보고되었다 [4]. 만성 골수성 백혈병은 무기력, 체 중 감소, 출혈, 식은 땀, 빈혈, 및 비장 비대증(splenomegaly)을 포함하는 증상이 있음에도 불구하고, 환자의 약 50%는 증상이 없어 혈액 검사로 진단되는 경우가 많다 [15].…”
Section: 서 론unclassified